Reserve Bank in the market place - Grenville, Stephen; Battellino, Ric.; Laker, John.; Reserve Bank of Australia (Sydney : The Bank, 1990)
Three senior Reserve Bank officers speak about monetary policy, domestic market operations and foreign exchange market operations. The three talks give a very clear picture of why and how the Reserve Bank implements monetary policy.
The operation of monetary policy / Stephen Grenville -- The Reserve Bank's domestic market operations / Ric Battellino -- The Reserve Bank's foreign exchange market operations / John Laker.
Subtitle from container.
Keywords: Reserve Bank of Australia; Banks and banking, Central -- Australia; Monetary policy -- Australia; Foreign exchange